PENANGGULANGAN BAHAYA NARKOBA DAN KENAKALAN REMAJA DI WILAYAH KEJAKSAAN NEGERI SIJUNJUNG - Khairani Khairani; Fadhilah Sabri; Aria Zurnetti; Fengki Andreas (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
This activity is carried out to provide understanding and skills to adolescents, in this case, high school children, so that they can avoid the dangers of drugs. This event's importance is because drugs in society are very evenly distributed. After all, not only adults who use them, even children, have become drug addicts. The abuse of narcotics has shown the importance of narcotics because it has reached the younger generation. If the younger generation becomes damaged due to narcotics abuse, it will endanger this nation's baton. This condition raises public unrest, especially parents who have teenage children and school-age children. This training is based on problems, how adolescents understand drugs, what steps need to be taken so that teenagers avoid drug abuse. The method used is to first provide knowledge to adolescents about the types of drugs and the dangers of improper use, then perform simulations to avoid drugs. Considering a large number of drug abuse has been very concerning, the Master of Law Program conducts training to overcome the dangers of drugs for school children at SMA Negeri Sijunjung in one form of prevention to avoid the dangers caused by drugs. The results of this activity show that, in general, adolescents in Sijunjung already know about the dangers of drug use. However, they do not know the types of drugs available and how they should avoid the threat of drug trafficking, which is very widespread in society.